Chromosome-level genome assembly of the ratmouth barbel, Ptychidio jordani - Yuanyuan Wang; Yexin Yang; Yuli Wu; Yi Liu; Qingyong Li; Chao Liu; Zhiyong Jiang; Wanying Jiang; Fangcan Chen; Xidong Mu (Scientific Data)
Abstract The ratmouth barbel (Ptychidio jordani) is a critically endangered freshwater fish from the Cyprinidae family, primarily due to overfishing and habitat disruption. To address the challenges of its shrinking wild populations and the difficulties in artificial reproduction, we sequenced, assembled, and annotated a high-quality chromosome-level genome of P. jordani using next-generation short-read sequencing, third-generation long-read sequencing, and Hi-C sequencing. The final genome assembly was 1.14 Gb, consisting of 25 chromosomes with a contig N50 of 25.14 Mb and a scaffold N50 of 42.91 Mb. We identified 25,183 protein-coding genes, 751.75 Mb of repeats, and 19,373 ncRNAs. Methylation loci on most chromosomes ranged from 1,000 to 3,000 per 100 kb window. Gene expression levels across various tissues were analyzed, revealing 12,135 (caudal fin), 11,465 (liver), 14,438 (gill), 12,413 (heart), 8,301 (spleen), and 3,578 (kidney) differentially expressed genes compared to muscle. The comprehensive genomic and transcriptomic resources generated here will aid in understanding the ecology, adaptation, and environmental responses of P. jordani, supporting future research and conservation efforts.